Evaluation of serum zinc level in patients with Alopecia Areata - Ivan Abdullah; Sangar Othman (المجلة العراقية للصيدلة, 2022)
Background: Alopecia areata (AA) is non-scarring telogenic alopecia of autoimmune etiology. Clinically, the disease is characterized by the appearance of alopecic patches or plaques of varying size and number on the scalp with peak incidence 2% in the general population, can involve any age group with higher prevalence in younger patients. Aim: The purpose of this study is to estimate serum zinc level in patient with alopecia areata comparing to age, sex match healthy controls. Method: A case-control study was conducted on total number of 120 subjects;60 patients with AA and 60 age- and sex matched healthy controls. Serum zinc levels were assessed in all subjects. Comparison of mean serum zinc levels was done between all patients and controls. A significantly lower serum zinc level was found in patients with AA compared with controls and the significant inverse correlations existed between serum zinc level and severity of AA.